Cardiologic Manifestations in Omicron‐Type Versus Wild‐Type COVID‐19: A Systematic Echocardiographic Study - Eihab Ghantous; Aviel Shetrit; Aviram Hochstadt; Ariel Banai; Lior Lupu; Erez Levi; Yishay Szekely; Nadav Schellekes; Tammy Jacoby; David Zahler; Tamar Itach; Philippe Taieb; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Information about the cardiac manifestations of the Omicron variant of COVID‐19 is limited. We performed a systematic prospective echocardiographic evaluation of consecutive patients hospitalized with the Omicron variant of COVID‐19 infection and compared them with similarly recruited patients were propensity matched with the wild‐type variant. Methods and Results A total of 162 consecutive patients hospitalized with Omicron COVID‐19 underwent complete echocardiographic evaluation within 24 hours of admission and were compared with propensity‐matched patients with the wild‐type variant (148 pairs). Echocardiography included left ventricular (LV) systolic and diastolic, right ventricular (RV), strain, and hemodynamic assessment. Echocardiographic parameters during acute infection were compared with historic exams in 62 patients with the Omicron variant and 19 patients with the wild‐type variant who had a previous exam within 1 year. Of the patients, 85 (53%) had a normal echocardiogram. The most common cardiac pathology was RV dilatation and dysfunction (33%), followed by elevated LV filling pressure (E/e′ ≥14, 29%) and LV systolic dysfunction (ejection fraction <50%, 10%). Compared with the matched wild‐type cohort, patients with Omicron had smaller RV end‐systolic areas (9.3±4 versus 12.3±4 cm2; P=0.0003), improved RV function (RV fractional‐area change, 53.2%±10% versus 39.7%±13% [P<0.0001]; RV S′, 12.0±3 versus 10.7±3 cm/s [P=0.001]), and higher stroke volume index (35.6 versus 32.5 mL/m2; P=0.004), all possibly related to lower mean pulmonary pressure (34.6±12 versus 41.1±14 mm Hg; P=0.0001) and the pulmonary vascular resistance index (P=0.0003). LV systolic or diastolic parameters were mostly similar to the wild‐type variant‐matched cohort apart from larger LV size. However, in patients who had a previous echocardiographic exam, these LV abnormalities were recorded before acute Omicron infection, but not in the wild‐type cohort. Numerous echocardiographic parameters were associated with higher in‐hospital mortality (LV ejection fraction, stroke volume index, E/e′, RV S′). Conclusions In patients with Omicron, RV function is impaired to a lower extent compared with the wild‐type variant, possibly related to the attenuated pulmonary parenchymal and/or vascular disease. LV systolic and diastolic abnormalities are as common as in the wild‐type variant but were usually recorded before acute infection and probably reflect background cardiac morbidity. Numerous LV and RV abnormalities are associated with adverse outcome in patients with Omicron.